The relative age effect and the relationship between biological maturity and athletic performance in Austrian elite youth soccer players - Wenger, M.; Csapo, R. (Frontiers in Sports and Active Living, 2025)
Purpose: Publications from recent years suggest that the biological developmental stage of underage athletes has a significant impact on their athletic performance. This scientific study is the first quantitative attempt in Austria to investigate the impact of the relative age effect and biological maturity on the physical performance of young elite soccer players.